Analysis of long-period and short-period fiber Bragg gratings by phase matching condition - Liu, Yu; Lee, Sang B.; Park, Tae S.; Jo, Kyu M.; Choi, Sang Sam (Proceedings of SPIE - The International Society for Optical Engineering, 1996)
Using grating phase vector and the phase matching condition, universal formation for fiber Bragg grating was constructed, which can be directly applied for the analysis of long- period fiber grating band rejection filters, short-period reflection filters and short-period band rejection filter (tilted grating).